A new dichloro-substituted benzyl alcohol derivative from the rhizomes of Curculigo capitulata (Lour.) Kuntze - Viet Hau Dang* , Thi Trang Phan, Thi Hue Nguyen, Thi Thu Trang Nguyen, Thi May Nguyen, Thi Loan Le, Thi Hong Anh Nguyen, Minh Khoi Nguyen, Van Tai Nguyen (Vietnam Journal of Science, Technology and Engineering, 2025)
Curculigo capitulata (Lour.) Kuntze’s rhizomes have been utilised in traditional medicine for the treatment of various diseases, such as kidney stones, high blood pressure, nephritis, and cystitis. To date, there has been limited research on its chemical constituents in Vietnam. A phytochemical investigation of the ethyl acetate extract from C. capitulata’s rhizomes led to the isolation of five compounds, including a novel dichlorophenolic derivative, named capitulatol A (1), and four known compounds: O-orsellinaldehyde (2), cinnamic acid (3), orcinol (4), and orcinol glucoside (5). Their structures were elucidated using 1D and 2D nuclear magnetic resonance (NMR) spectroscopic and high-resolution electrospray ionisation-mass spectrometry (HRESI-MS) data, along with comparisons to previously published references. Compound 1 has not been described before, while compounds (2-4) have been isolated from this plant for the first time. These results indicate that phenolics and phenolic glucosides are the main components, which can serve as significant markers for the chemotaxonomy of the herb. Moreover, this chemical information will enhance our understanding of this plant, both in Vietnam and globally. Furthermore, the findings can be applied to further research in pharmacology and clinical medicine in the future.